2014
DOI: 10.1039/c4cc05765a
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective synthesis of α-(aminomethyl)-γ-butyrolactones via a catalyst-free aminolactonization

Abstract: An auto-catalytic domino reaction, presumably involving an aza-Michael reaction, proton transfer, and lactonization, furnishing α-(aminomethyl)-γ-butyrolactones in near quantitative yields and excellent diastereoselectivity is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Enynes 2a–2u and the carboxylic acid precursors for the preparation of NHPI esters 1h , 1i , and 1m were synthesized according to previous reports in the literature. …”
Section: Methodsmentioning
confidence: 99%
“…Enynes 2a–2u and the carboxylic acid precursors for the preparation of NHPI esters 1h , 1i , and 1m were synthesized according to previous reports in the literature. …”
Section: Methodsmentioning
confidence: 99%
“…The following MBH alcohols were prepared by using GP2 and their spectral data correspond with published data: Methyl 2-(hydroxy(phenyl)methyl)acrylate (9′a), 28 methyl 2-(hydroxy(4tolyl)methyl)acrylate (9′b), 28 methyl 2-((4-bromophenyl)(hydroxy)methyl)acrylate (9′c), 28 methyl 2-((4-cyanophenyl)(hydroxy)methyl)acrylate (9′d), 29 methyl 2-((2-bromophenyl)(hydroxy)methyl)acrylate (9′f), 28 methyl 2-((3-bromophenyl)(hydroxy)methyl)acrylate (9′g), 28 benzyl 2-(hydroxy(phenyl)methyl)acrylate (9′i), 29 and tert-butyl 2-(hydroxy(phenyl)methyl)acrylate (9′j). 29…”
Section: Preparation Of Mbh Alcohols 9′; General Procedures Gp2mentioning
confidence: 80%
“…First, we used 2‐arylthio aryl ester 3 a as a raw material and successfully obtained the corresponding arylcarboxylic acid derivative 4 a in an alkaline environment [26] . The reduction experiment showed that the ester group could be reduced under mild conditions when LiAlH 4 was used as reducing agent, and the yield of 4 b was 97 % [27] . After that, we tried to use 2‐arylthio aryl ester to synthesize a benzyl isothiazole compound.…”
Section: Resultsmentioning
confidence: 99%
“…[26] The reduction experiment showed that the ester group could be reduced under mild conditions when LiAlH 4 was used as reducing agent, and the yield of 4 b was 97 %. [27] After that, we tried to use 2-arylthio aryl ester to synthesize a benzyl isothiazole compound. To our delight, 3 a was successfully converted into the ideal product 4 c under the action of ammonium formate and iodobenzene diacetate.…”
Section: Resultsmentioning
confidence: 99%